Disunion Among Ourselves : The Perilous Politics of the American Revolution - Merritt, Eli (Book collections on Project MUSE., 2023)
"Disunion Among Ourselves tells the story of the deep political divisions that almost tore the Union apart in the 1770s and 1780s. So fractious were the founders' political fights that they feared the War of Independence might end in disunion and civil war. Instead of disbanding into separate regional confederacies, however, the founders united through self-sacrifice and compromise. They succeeded in holding the young nation together in part by transcending the baser angels of their natures. Yet, more even than this, they overcame division and disunion because they knew, concretely, that political unity was the best hope for preserving the life, liberty, and happiness of the American people"--